Pengaruh Fasilitas Terhadap Repurchase Intention di Objek Wisata Saparandaman Pool dan Café Kabupaten Solok Selatan - Filzah Abdul Hamdani; Kasmita Kasmita (Universitas Negeri Padang, 2022)
The research was conducted because of several problems that arise in the Saparandaman pool and cafe, namely the complaints of visitors about the available facilities and influencing the desire of visitors to come back to the Saparandaman pool and cafe. This is evidenced by the reviews of visitors who complain about the inadequate and inadequate facilities available. In addition, the number of visitor visits is not stable and tends to decrease every month. This study intends to find out the extent of the influence of facilities on the repurchase intention of visitors at the Saparandaman pool and cafe. This research is a quantitative type using a causal associative approach. The population used is visitors who come to the Saparandaman pool and cafe. The sampling technique used purposive sampling using special criteria so that 95 samples were obtained. By using a structured questionnaire according to the Likert scale which is tested for validity and reliability. Hypothesis testing using a simple linear regression test. From the research that has been carried out, it is known that the facilities at the Saparandaman pool and cafe are in the bad category at a percentage of 54%, while repurchase intention is in the bad category at a percentage of 54%. Based on the results of hypothesis testing, the calculated F value is 10,046 with Sig 0.002 <0.05 so that Ha is obtained. Then obtained F count of 10,046 in sig. 0.002 <0.05, it is concluded that the facility has an effect on repurchase intention. Regression coefficient 0.241 with sig 0.002 <0.05. This means that each additional 1 unit of the facility can add 0.241 repurchase intention. R Square value of 0.097 which concluded that the influence of the facility variable on repurchase intention was 9.7% and 90.3% was determined by other factors.